First systematic study of late pleistocene rat fossils from Batu Caves: new record of extinct species and biogeography implications - Ishlahuda Hani Sahak,; Lim, Tze Tshen; Ros Fatihah Muhammad,; Nur Syimah Izzah Abdullah Thani,; Mohammad Amin Abd Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper presents the first systematic study of rat (Murinae) isolated dental fossils collected from Late Pleistocene (66000 years ago) cave breccia deposits in Cistern Cave, Batu Caves, Selangor. The cave is partly deposited with fine, coarse and pebbly breccia mixed with abundant mammal fossil cemented to the wall and ceiling of the cave. A total of 39 specimens of teeth and jaw fragments of Murinae were recovered among other large and small mammal remains. Dental morphology and size comparisons suggest that the fossils belong to extinct and extant species which occurred in Peninsular Malaysia and adjacent regions. The species identified are Chiropodomys gliroides, Leopoldamys sabanus, Leopoldamys minutus, Maxomys whiteheadi, Maxomys rajah and Rattus rattus. Almost all species identified from the fossils are known as markers for lowland forested environments.